Women in performance : repurposing failure - Gorman, Sarah. 1969- (London ; New York : Routledge, 2021)
"Women in Performance charts the renewed popularity of intersectional feminism, gender, race and identity politics in contemporary Western experimental theatre and performance through the featured artists' ability to strategically repurpose failure. Failure has provided a popular frame through which to theorise recent avant-garde performance, even though the work rarely acknowledges stakes tend to be higher for women than men. This book analyses the imperative work of a number of female, non-binary and trans* practitioners who resist the postmodern doctrine of 'post-identity' and attempt to foster a sense of agency on stage. By using feminism as a critical lens, Gorman interrogates received ideas about performance failure and negotiates contradictions between contemporary white feminism, intersectional feminism, gender and sexuality. Women in Performance reveals how performance has the power to both observe and reject contemporary feminist and postmodern theory, rendering this text an invaluable resource for Theatre and Performance Studies students and those grappling with the disciplinary tensions between Feminism, Gender, Queer and Trans* Studies"--
Introduction: Female Performers - Do They Matter? -- Essentialism, Negativity and the Rebirth of Identity Politics -- Taking Back Control: Invective, Irony and Inscrutability -- Self-Care and Radical Softness: Refusing Neoliberal Resilience -- Nightclubbing: Queer Heterotopia and Club Culture -- Taking Pleasure: Binary Ambivalence and Transgression -- Tempering Anger: Asserting the Right to Define as Comic Without Further Caveat -- Afterword.
Includes bibliographical references and index.
Keywords: Women in the theater; Women in the performing arts; Failure (Psychology); Performance -- Psychological aspects; Theater -- Psychological aspects; Feminism and theater